Topical versus intravenous tranexamic acid use in total knee arthroplasty. Issue 5 (September 2016) - Arntson, Zach; Ferguson, Adam; Markel, David C.
Abstract : Background: Topical or intravenous application of tranexamic acid (TXA) during total knee arthroplasty has been shown to reduce postoperative bleeding and transfusion rates. The objective of this study was to compare the efficacy and safety of topical and intravenous TXA at a single institution. Methods: Four hundred and eighty-two patients were reviewed retrospectively, with 166 patients included as a non-TXA control group, and 70 in the topical TXA group and 48 in the intravenous TXA group. The primary outcomes were transfusion rates and blood loss calculated from the difference between preoperative and postoperative hemoglobin levels. Thromboembolic complications were recorded up to 90 days postoperatively. Results: After TXA use, the mean hemoglobin levels were significantly higher in the topical (10.5 g/dL) and intravenous TXA groups (10.4 g/dL) when compared to the control group (9.6 g/dL) ( P <0.001). This resulted in ∼18% less blood loss postoperatively when comparing both the intravenous and topical cohorts. The transfusion rate for the control group (12.7%; 21/166) was higher than rates for the intravenous (2.1%; 1/48) and topical (4.3%; 3/70) TXA cohorts ( P =0.023). There were no differences in complication rates among cohorts. Conclusions: During cemented total knee arthroplasty, both topical and intravenous application of TXA resulted in significant reductions in postoperative bleeding and transfusion rates. There were no statistically significant changes in complication rates in either treatment group compared with the control group. Both topical and intravenous TXA appeared safe and effective in reducing postoperative bleeding and transfusion rates in cemented total knee arthroplasty.